2014
DOI: 10.3389/fmicb.2014.00408
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized self-replication under fast PCR cycling conditions yields Taq DNA polymerase mutants with increased DNA-binding affinity and blood resistance

Abstract: Faster-cycling PCR formulations, protocols, and instruments have been developed to address the need for increased throughput and shorter turn-around times for PCR-based assays. Although run times can be cut by up to 50%, shorter cycle times have been correlated with lower detection sensitivity and increased variability. To address these concerns, we applied Compartmentalized Self Replication (CSR) to evolve faster-cycling mutants of Taq DNA polymerase. After five rounds of selection using progressively shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Increasing evidence has suggested that rapid acquired therapeutic resistance is the major cause of the failure of standard comprehensive treatments, leading to the recurrence and high mortality of glioma . Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma . Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has suggested that rapid acquired therapeutic resistance is the major cause of the failure of standard comprehensive treatments, leading to the recurrence and high mortality of glioma . Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma . Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Various molecular pathways have been shown to be responsible for the acquisition of therapeutic resistance in glioma. 26,[31][32][33] Therefore, it is essential to identify the mechanisms, especially prognostic biomarkers, underlying therapeutic resistance in glioma. In this study, we analyzed the transcriptome expression profiles of 3 published GEO databases related to pathological classification, radioresistance, and TMZ resistance and identified TRIB2…”
Section: Discussionmentioning
confidence: 99%
“…Following heat treatment to degrade the components of the cell, only the polymerase and its template gene remain in the emulsion, and a PCR reaction can be initiated by polymerase variants that are functional under conditions that can be customized to select for numerous desired phenotypes. The CSR scheme has been used to generate novel DNA polymerases with a number of unique features, including increased thermostability, the ability to bypass blocking lesions, increased DNA binding affinity, resistance to inhibitors, and decreased uracil binding (Arezi et al, 2014;Ghadessy et al, 2001Ghadessy et al, , 2004Tubeleviciute and Skirgaila, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(3) Either (a) compartmentalized self-replication (CSR) is performed under selective conditions to preferentially amplify the genes of productive DNA polymerases (green circles) rather than unproductive DNA polymerases (red polygons) (Ghadessy et al, 2001) or (b) compartmentalized self-tagging (CST) is performed to tag productive polymerase genes with a biotin-labeled primer before (4) streptavidin precipitation . These schemes have been used to generate new polymerases with increased thermostability, the ability to bypass blocking lesions, increased DNA binding affinity, resistance to inhibitors, decreased uracil binding, and, ultimately, synthesis of unnatural genetic polymers (Arezi et al, 2014;Ghadessy et al, 2001Ghadessy et al, , 2004Tubeleviciute and Skirgaila, 2010). Green bars represent genes for productive polymerase variants; red bars represent genes for unproductive polymerase variants.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers characterize DNA polymerases that tolerate PCR inhibitors and allow rapid DNA amplification from clinical samples without DNA purification, thereby reducing analysis time, cost, and potential for contamination. The contribution by Killelea et al demonstrates that a Family D polymerase from Pyrococcus abysii is tolerant to high concentrations of PCR inhibitors while Arezi and colleagues describe a method to select for DNA polymerase variants that enable direct PCR from whole blood (Arezi et al, 2014;Killelea et al, 2014).…”
mentioning
confidence: 99%